PENGARUH PEMBERIAN DOLOMIT PADA KOSENTRASI YANG BERBEDA TERHADAP PERTUMBUHAN JAMUR TIRAM - Guslinar Halawa (Universitas Nias Raya, 2023)
This study aims to determine the effect of dolomite administration at different concentrations on the growth of oyster mushroom(Pleurotus Ostreatus). This typi of research is a descriptive quatitativereseacth with a pure experimental method (True Experiment). The sample in this study is all oyster mushrooms (Pleurotus Ostreatus) that have been bred, consisting of 24 baglogs, the results of each treatment applied were: the first for the measurement of leaf area, namely P0=15,1 cm, P1=59 cm, P2=75 cm, P3=25,89 cm, P4=64,83, P5=107 cm.The second is the number of mushroom fruiting bodies, namely: P0=9pieces, P1=8 pieces, P2=6,pieces, P3=9,75 pieces, P4=6,75 lpieces, P5=8,25pieces,and the third is the weight of oyster mushroom leaves namely: P0=3,67 grams, P1=5,65 grams, P2=6,075 grams, P3=7,47 grams, P4=7,22 grams, P5=11,21 grams. The data in this is study were analyzed by normality test, homogeneity test and hypothesis testing using the SPSS 15.0 application. Based on the results of the study showed that there was an effect of using dolomite as a growth of oyster was an effect of using dolomite as a growthregulator on the growth of oyster mushrooms (Pleurotus Ostreatus). In each treatment and replication, starting from the first treatment to the fifth treatment, the best growth of oyster mushroom was 50 grams (5th treatment). Suggestions from reseachers are that people should be able to use dolomite lime as a growth regulator for oyster mushrooms (Pleurotus Ostreatus).